Black women mothering & daughtering during a dual pandemic : writing our backs - Evans-Winters, Venus E. (Research, advocacy, collaboration, and empowerment mentoring series., 2024)
The contributors of this volume share with the scholarly community how they have learned to strive, resist, adapt, and re-conceptualize Black women's mental health and labor during the dual pandemics of white supremacy and COVID-19. This book is unique in that it calls for the contributing authors to draw upon and reflect on the use of sisterhood and a literacy circle to cope with an economic crisis, mass death, and racial battle fatigue during a worldwide pandemic. Specifically, the invited authors draw inspiration from Venus E. Evans-Winters' book Black Feminism in Qualitative Inquiry: A Mosaic for Writing Our Daughter's Body as an exemplar of research that both centers the issues and concerns of Black women scholar-practitioner-activists and presents a methodology consistent with Black feminist ways of knowing and expressions. Evans-Winters' theoretical and methodological writings are among the first works in research and gender studies that have successfully interwoven Black feminists' politics, spirituality, and Africanism with educational research and thought. Using constructed stories from the authors' personal narratives, Black Women Mothering and Daughtering During a Dual Pandemic: Writing Our Backs addresses themes pertinent to Black women's lives, including our socialization and socio-emotional development, mother/daughter and other mother-daughter relationships, navigating the racial politics of schooling, friendships, survivorship, and grief using non-normative methodological concepts and practices.The authors explore concepts such as daughtering, politicking, mother speak, and cultural exchange while employing linguistic expressions such as prose, text messages, dialogue, and personal narrative--firmly planted in authentic Black womanist aesthetics. Furthermore, the authors highlight and demonstrate why and how they utilize reading and Black women's literary works to critically reflect, meaningfully write, heal, and do their work in times of peril (Morrison, 2019). More specifically, this book explores how the authors draw from Black women's cultural literacies in teaching, healing, mentoring, and activism. How are Black women's literary works as a body of knowledge used in healing spaces to marshal new or forgotten healing methodologies, cultural frame of references, and spiritual awakenings? The contributing authors address this question from multiple perspectives, such as education, social work, and psychology.Collectively, the authors advance Black women's mental wealth as a theoretical and methodological healing modality that meets their multiple identities as spiritual and cultural beings, educators, daughters, mothers, sisters, healers, and social activists. This is the first anthology to explore how Black women's literacy during a state of racial unrest and resistance alongside a global health pandemic shapes our cultural knowledge, ways of coping, and spiritual endeavors across varied-and often ambiguous contexts.